Shiva in the form of Natesha - Temples of India Project Team (Jio Institute, 2024)
The panel depicting Shiva in his dancing form, Natesha, might have once been placed at the ceiling of a lost Shaiva temple on Harsha Hill. It is now housed in the Government Museum, Sikar. In the depiction, Natesha is surrounded by various dancers and musicians. He gracefully holds a damru in his right hand and likely a trident in his left hand, which is significantly damaged. The tightly cloistered figures of dancers and musicians in action and angular postures not only provide visual centrality to the figure of the dancing Natesha but also enhances the rhythmicity of the scene. On his immediate left is a musician holding a pakjavaja drum. Positioned centrally, the instrument fills the squarish space between Natesha and a dancer on the sides and between the face of the drummer and dwarf at the bottom. Even though Natesha is not commonly depicted as an independent sculpture in Rajasthan temples, he often occupies prominent architectural spaces, such as above the doorway of the main temple at Baroli, as well as at Neelkanth and the later Chauhan Temple at Adhai-din-ka-jhonpra. In the depiction, Natesha is surrounded by various dancers and musicians. He gracefully holds a damru in his right hand and likely a trident in his left hand, which is significantly damaged. The tightly cloistered figures of dancers and musicians in action and angular postures not only provide visual centrality to the figure of the dancing Natesha but also enhances the rhythmicity of the scene. On his immediate left is a musician holding a pakjavaja drum. Positioned centrally, the instrument fills the squarish space between Natesha and a dancer on the sides and between the face of the drummer and dwarf at the bottom.